Analysis of the Effect of the Application of Total Quality Management (TQM) on Performance Improvement through Leadership - Dewi Kholifatul Ummah; Saiful Bukhori; Dewi Rokhmah (Universitas Negeri Semarang, 2023)
The results of the study indicate that there is a direct and indirect effect. Total Quality Management (TQM) is a method used by customer satisfaction oriented companies to improve managerial performance. This study aims to determine the direct and indirect effect of TQM on performance through leadership as a moderating variable. The research method is a quantitative research conducted at the Jatibanteng Public Health Center. The number of samples in the study was 73 with a sampling technique using the entire total population. Analysis of the data used is using smartPLS. First, leadership has a direct effect on employee performance with a t statistic of 8,581. Second, TQM has a direct effect on leadership with a t statistic of 54.377. Third, TQM has a direct effect on employee performance with a t statistic of 11.762. Fourth, the results of the analysis of P value < 0.005 means that there is an indirect effect between TQM on employee performance, which can also be interpreted if the intervening variable (leadership) plays a role in mediating the relationship between TQM and employee performance.